2022
DOI: 10.3390/s22072652
|View full text |Cite
|
Sign up to set email alerts
|

Force-Sensitive Interface Engineering in Flexible Pressure Sensors: A Review

Abstract: Flexible pressure sensors have received extensive attention in recent years due to their great importance in intelligent electronic devices. In order to improve the sensing performance of flexible pressure sensors, researchers are committed to making improvements in device materials, force-sensitive interfaces, and device structures. This paper focuses on the force-sensitive interface engineering of the device, which listing the main preparation methods of various force-sensitive interface microstructures and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 19 publications
(6 citation statements)
references
References 150 publications
0
5
0
Order By: Relevance
“…Compared with the unpatterned PDMS, the microstructured PDMS films enable the device to respond to a wider pressure range with smaller error bars . It is observed that the extent of decrease in Δ I / I 0 reduces with increasing grit sizes of the films, as the size reduction in microstructures increases the compression resistance and leads to reduced film deformation. For the distribution of microstructures, a larger size is beneficial for increased sensitivity, while a smaller size can reduce the hysteresis caused by the interface adhesion. , Although significant change ratios of −54.1 and −52.1% are obtained respectively from PDMS 320# and PDMS 800# , an undesired asymmetric distribution between photocurrent levels is found during loading and unloading. By adopting the PDMS 2000# film with a higher density of a smaller microstructure, a hysteresis of 0.87% in the pressure range of 0–300 kPa is achieved.…”
Section: Resultsmentioning
confidence: 99%
“…Compared with the unpatterned PDMS, the microstructured PDMS films enable the device to respond to a wider pressure range with smaller error bars . It is observed that the extent of decrease in Δ I / I 0 reduces with increasing grit sizes of the films, as the size reduction in microstructures increases the compression resistance and leads to reduced film deformation. For the distribution of microstructures, a larger size is beneficial for increased sensitivity, while a smaller size can reduce the hysteresis caused by the interface adhesion. , Although significant change ratios of −54.1 and −52.1% are obtained respectively from PDMS 320# and PDMS 800# , an undesired asymmetric distribution between photocurrent levels is found during loading and unloading. By adopting the PDMS 2000# film with a higher density of a smaller microstructure, a hysteresis of 0.87% in the pressure range of 0–300 kPa is achieved.…”
Section: Resultsmentioning
confidence: 99%
“…Pressure-based text entry is also proposed for smartphones [17,18] which has drawbacks like error-proneness.…”
Section: Related Workmentioning
confidence: 99%
“…To overcome this, the incorporation of high-deformation materials as electrodes or dielectric layers, in tandem with the engineering of microstructures on these components, enhances sensitivity even under minimal pressure. Various microstructures have been employed on electrodes or dielectric layers, such as pyramids, columns, microspheres, , and patterns molded from natural plants with micro/nanostructures. Despite these advancements, limitations continue to exist with respect to sensitivity, operational pressure range, and methodological complexity.…”
Section: Introductionmentioning
confidence: 99%